Bone marrow fat distribution in patients with β-thalassemia: a study using chemical shift-based water-fat MRI - Ismail, Umi Nabilah; Azlan, Che Ahmad; Khairullah, Shasha; Azman, Raja Rizal; Lee, Kuan Jin; Yeong, Chai Hong; Omar, Nur Farhayu; Ramli, Norlisah; Md Shah, Mohammad Nazri; Jackson, Nicholas; Ng, Kwan Hoong (Association of University Radiologists, 2022)
Rationale and Objectives: Molecular studies have shown the changes in bone marrow fat in relation to altered hematopoiesis. This study aims to investigate the changes in the bone marrow fat in patients affected by β-thalassemia by using chemical shift-encoded (CSE)–MRI.